Polyethyleneglycols effectively increase the liposome concentration in blood circulation - Ishikura, Chiyoji; Yuda, Tsutomu; Maruyama, Kazuo; Okamoto, Aki; Iwatsuru, Motoharu (Drug Delivery System, 1991)
The effect of polyethyleneglycol (PEG, 1800, 5000 and 12000 in molecular weight) on biodistribution of liposomes composed of egg phosphatidylcholine/cholesterol (PC/CH=1 : 1 in molar ratio) was examined in mice. PC/CH liposomes have been cleared from blood(3.5% of dose)and taken up by liver and spleen (60.0% and 6.6% of dose, respectively)3h post injection. Incorporation of lipophilic PEG derivatives or ganglioside GM1 increased the liposome concentration in blood and avoided the uptake by reticuloendothelial system. Liposomes composed of PEG with 5000 in molecular weight showed the highest blood concentration with 59.1% of injected dose at 3h post injection. This PEG's activity to increase the liposome concentration is greater than that of the ganglioside GM1, a well described glycolipid with this activity. PEG with 12000 in molecular weight also played liposomes to increase their concentration in blood with a similar level of GM1. PEG with low molecular weight such as 1800 showed relatively lower activity than above mentioned PEG and GM1. Present data indicate that lipophilic PEG can significantly avoid RES uptake, concomitantly enhance the liposome concentration in the circulation.